Quality of life related to health and comorbidity in mastectomized patients - Santos, Míria Conceição Lavinas; Silva, Tiago Barreto de Castro e; Cavalcante, Kamila Monteiro; Souto, Natasha Firmino; Lôbo, Sâmya Aguiar; Fernandes, Ana Fátima Carvalho (Rev Rene, 2011)
This study aimed to assess the association between comorbidities and quality of life of mastectomized women. This cross-sectional study was carried out with 48 women, with an average age of 58.2 years and 55.4 months after the surgery. There was a support group (n=16) and a control group (n=32) from a hormone therapy outpatient clinic of a reference hospital in Fortaleza/Brazil. It was the Medical Outcomes Study Questionaire 36 — Item Short Form Survey (SF-36). The groups differed from each other with regard to comorbidities: 68.8% in the study group and 31.2% in the control group (p=0,029). Considering both groups, we could evidence the worst scores related to the dimension Role Limitations due to Physical Health Problems (p=0,143), and the best scores related to the dimension Social Functioning (p=0.272). The combination of three comorbidities have determined a lower level of QoL on the dimensions Physical Functioning (p=0.463), Bodily Pain (p=0.869), and General Health (p=0.138).